Exploring Students’ Perceptions of Problem Based Learning (PBL) in Enhancing Speaking Skill at SMP Muhammadiyah 3 Bandar Lampung - Winda Puspitasari; M. Ridho Kholid; M. Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigated the effectiveness of problem-based learning (PBL) in improving junior high school students' English speaking ability. A case study of students at SMP Muhammadiyah 3 Bandar Lampung showed that students generally had positive perceptions of PBL. They felt that PBL made learning more interesting and encouraged them to participate more actively. The results showed improvements in self-confidence, vocabulary mastery, and ability to interact in English. However, students still faced challenges in terms of grammar and pronunciation mastery. This study concluded that PBL can be an effective approach to improving students' speaking ability, but it needs to be supported by additional activities to overcome existing obstacles.